2021
DOI: 10.3324/haematol.2021.278399
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib or bortezomib in combination with cyclophosphamide and dexamethasone followed by carfilzomib maintenance for patients with multiple myeloma after one prior therapy: results from a multicenter, phase II, randomized, controlled trial (MUK<i>five</i>)

Abstract: The proteasome inhibitors (PIs), carfilzomib and bortezomib, are widely used to treat myeloma but head-to-head comparisons have produced conflicting results. We compared the activity of these PIs in combination with cyclophosphamide and dexamethasone (KCd vs VCd) in second line treatment using fixed duration therapy and evaluated the efficacy of carfilzomib maintenance. MUKfive was a phase II controlled, parallel group trial that randomised patients (2:1) to KCd (201) or VCd (99); responding patients on carfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…The benefit in TTP for carfilzomib‐dexamethasone maintenance compared with no maintenance was in general consistent across different subgroups, including cytogenetic status. This observation is consistent with the recently published MUKfive study where carfilzomib maintenance was associated with an approximate increase of 6 months in PFS compared with no maintenance in patients treated with CAR‐CY‐DEX at first relapse 26 . In contrast to our study the MUKfive study did not include consolidation with salvage ASCT or use of dexamethasone in the maintenance phase.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The benefit in TTP for carfilzomib‐dexamethasone maintenance compared with no maintenance was in general consistent across different subgroups, including cytogenetic status. This observation is consistent with the recently published MUKfive study where carfilzomib maintenance was associated with an approximate increase of 6 months in PFS compared with no maintenance in patients treated with CAR‐CY‐DEX at first relapse 26 . In contrast to our study the MUKfive study did not include consolidation with salvage ASCT or use of dexamethasone in the maintenance phase.…”
Section: Discussionsupporting
confidence: 92%
“…The toxicity observed during CAR‐CY‐DEX induction and following the subsequent salvage ASCT were comparable with the level of adverse events reported in other studies and particular the risk of cardio‐toxicity was in line with other studies 6,7,16,25,26 . The all‐cause day 100 mortality after salvage ASCT in our study was 1.1% which is in accordance with the day 100 mortality of 0 to 5% found in other salvage ASCT studies 5,8,25 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of GEM-KyCyDex study are consistent with those of other clinical trials that tested the KCd combination. The phase II MUK five trial 18 showed greater efficacy of KCd over VCd (bortezomib, cyclophosphamide, dexamethasone) in RRMM after one PL. In this study, carfilzomib was administered twice weekly at a dose of 36 mg/m 2 and oral Cy was given weekly (on days 1, 8 and 15) at a fixed dose of 500 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Carfilzomib/Cyclophosphamide/Dexamethasone Carfilzomib/cyclophosphamide/dexamethasone has been shown to be well tolerated with the toxicity profile of carfilzomib being similar to that seen in other trials. 38 A phase II trial (MUKfive) compared the safety and toxicity of carfilzomib/cyclophosphamide/dexamethasone with bortezomib/cyclophosphamide/dexamethasone in patients with relapsed/refractory MM, who had received one prior regimen. 38 A higher proportion of patients receiving carfilzomib experienced VGPR or better, and it was noninferior to bortezomib.…”
Section: Bortezomib/cyclophosphamide/dexamethasonementioning
confidence: 99%